Unspecified Sexual Dysfunction in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision—Diagnostic Classification, Systemic Assessment, and Clinical Intervention - Jimmie Manning (Psychiatry International, 2026)
Unspecified Sexual Dysfunction is a residual diagnostic category within the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR) used when symptoms characteristic of a sexual dysfunction cause clinically significant distress but do not meet criteria for a specific sexual dysfunction and the clinician does not specify the reason, including situations in which insufficient information is available for a more specific diagnosis. This narrative literature review examines diagnostic classification and clinical assessment in such presentations and considers how systemic perspectives can complement psychiatric assessment and intervention. A literature search using Google Scholar and citation-network mapping identified 34 peer-reviewed sources addressing sexual dysfunction classification, assessment, biopsychosocial and relational aspects of sexual distress, and treatment. The literature supports a distinction between diagnostic classification and comprehensive clinical formulation. Biological, psychological, relational, sociocultural, and developmental aspects do not constitute diagnostic criteria for Unspecified Sexual Dysfunction but may provide clinically relevant information for understanding sexual distress and selecting appropriate interventions. Systemic and relational assessment may therefore complement DSM-5-TR diagnosis by identifying interpersonal and contextual aspects relevant to treatment planning without redefining the diagnosis itself. Integrating diagnostic evaluation with broader clinical formulation may support individualized treatment and interdisciplinary collaboration across psychiatry, sexual medicine, psychosexual therapy, and relational or systemic care.